Penerapan Pemahaman Belajar Siswa Melalui Bimbingan Belajar Menggunakan Alat Peraga Cara Membuat Magnet - Januaris Pane; Ridana Laia; Bajongga Silaban; Nanny Lumbantobing; Asnida (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2022)
This service activity aims to provide students with an understanding of learning on physics material through the experimental method using teaching aids. The place where this activity was carried out was SMP N 1 Tapian Nauli. This activity is divided into several stages, the first is the introduction of students by the student-teacher, the second stage is the delivery of learning materials, and the third stage is conducting experiments through teaching aids that have been provided by the teacher. The last stage is conveying the conclusions from the experiments carried out. This activity provides benefits in increasing student understanding of physics learning through the experimental method. With the experimental method used, students become more active and can see directly the physical phenomena that occur through observation. The application of this tutoring through teaching aids is expected to increase students understanding of learning not only with theories and formulas.